Magnetic variation and power density of gravity driven liquid metal magnetohydrodynamic generators. (April 2018) - Ryan, Drew; Loescher, Corey; Hamilton, Ian; Bean, Robert; Dix, Adam
Highlights: Power density optimization performed for a gravity driven MHD system. Created a simple force balance model to analyze the average fluid velocity in the system. Determined that there is a maximum power density based on the applied magnetic field. Abstract: Magnetohydrodynamics (MHD) is the study of electrically conducting fluids flowing through applied magnetic fields. MHD can be applied in power generation to produce electricity with no moving mechanical parts. By not using mechanical parts, MHD generators may potentially produce electricity with low capital costs. This form of electrical generation can be paired with advanced nuclear reactors to make the reactors more economically competitive. This paper studies a vertical gravity driven MHD generator system, specifically maximizing the electrical power density output. For an MHD system, there will be a specific magnetic field that, when applied, will produce a maximum power density for the system.